Perceptions of Multimorbid Patients When Health Care Staff Accompany Family Physicians In Primary Care Settings - Youssef, Samira Mohammed; Alharthi, Maha Saad Nawahidh; Albalawi, Reem Nasser; albrahimi, Deemah; Shourbaji , Mansour; al sari , Wejdan ali; rasheed, Raghad abdulrahman; alhassn , Rehab hussain; Albargi , Almaha Barakat; Al Ali, Abdul Aziz Mohammed Ali; Bazuhayr , Naïf Mohamed saed (Journal of Ecohumanism, 2024)
Background: Multimorbidity, the presence of two or more chronic conditions in an individual, presents significant challenges in primary care, including fragmented care, higher healthcare costs, and difficulty in care coordination. Integrating nursing professionals into primary care teams has been proposed as a strategy to enhance access, improve care quality, and address these challenges. However, limited attention has been given to understanding patients’ perspectives, particularly those with multimorbidity, regarding the inclusion of health care staff in primary care practices. Methods: This qualitative descriptive study utilized semi-structured interviews to explore the perceptions of patients with multimorbidity toward the integration of health care staff in primary care settings. Participants were recruited from diverse healthcare environments, ensuring varied experiences with collaborative care models. Patients with five or more chronic illnesses were purposefully sampled, with interviews focusing on their experiences and expectations of health care staff involvement in primary care. Thematic analysis of interview transcripts was conducted using NVivo software, employing both inductive and deductive coding methods. Results: 28 participants with diverse chronic conditions were interviewed, with most expressing openness to health care staff involvement in primary care. Three central themes emerged: Expectations of Enhanced Care: Participants anticipated improved accessibility and continuity of care through health care staff integration but highlighted concerns about reduced access to physicians. Perception of the Health care staff ’s Role: While many viewed health care staff in supportive roles, others recognized their broader responsibilities in patient education, chronic disease management, and medication monitoring. Trust in health care staff ’ competence varied, with participants favoring physician oversight for complex tasks. Conditions for Effective Integration: Patients emphasized the need for clear role definitions, robust communication between health care staff and doctors, adherence to protocols, and continuity of care with the same health care staff to build trust. Conclusion: Patients with multimorbidity generally support the integration of health care staff into primary care teams, recognizing potential benefits in accessibility and care coordination. However, successful implementation requires clear delineation of roles, effective communication, and strategies to build trust. These findings highlight the importance of incorporating patient perspectives into healthcare system reforms to ensure collaborative care models meet their needs effectively.